PAQR5 Expression Is Suppressed by TGFβ1 and Associated With a Poor Survival Outcome in Renal Clear Cell Carcinoma - Tao, Chang; Liu, Wang; Yan, Xiang; Yang, Min; Yao, Si; Shu, Qiang; Li, Benyi; Zhu, Runzhi (Frontiers in Oncology, 2022)
Background: Renal cell carcinoma (RCC) was sex-hormone responsive, and clinical trials using progesterone significantly reduced the incidence of distal metastasis after radical nephrectomy. Recently membrane-bound progesterone receptors (mPRs) were discovered to mediate the non-genomic effect of progesterone. Aberrant expressions of these mPRs were reported in human breast, ovarian, urinary bladder, brain, uterine, and prostate cancers. However, their expression profiles in RCC are yet to be assessed. Methods: Multiple datasets from RNA sequencing (RNA-seq), cDNA microarray, and proteomic analysis were used to compare gene expression between cancerous and normal kidney tissues. Immunohistochemistry was conducted to examine protein expression in kidney tissues. Promoter methylation levels were assessed for correlation analysis with gene expression. Results: Of the seven membrane-bound progesterone receptor genes, the progestin and adipoQ receptor-5 (PAQR5) gene is predominantly expressed in normal kidney tissue but was significantly downregulated in RCC tissues. PAQR5 downregulation correlated with tumor stage, cancer grade, lymph node invasion, and distal metastasis only in clear cell RCC (ccRCC) tissues. PAQR5 downregulation was associated with an increased promoter DNA methylation and a poor survival outcome in ccRCC patients. In addition, PAQR5 expression inversely correlated with transforming growth factor beta-1 (TGFB1) expression, and TGFbeta1 treatment significantly reduced PAQR5 gene expression. Conclusion: PAQR5 is a novel prognostic biomarker in ccRCC and is negatively regulated by the TGFbeta1 pathway.